(untitled) (Fiep Bulletin - online, 2011)
This article derives from a Extension and Research Project in Special Physical Education. The Project is organized inside the LAR (Laboratory of Recreational Activities) – UNESP University, Presidente Prudente/SP. The LAR performs work of leisure-educational intervention in children with special educational needs and it takes a historical-cultural theory and psychomotor to understand the construction process of the human development. The main objective is to assess, identify and work on children psychomotor deficits. The LAR works with 46 children between 02 and 15 years who have psychomotor difficulties associated with learning problems, hyperactivity, behavior disorders, genetic syndromes, neurological disorders, among others. The children sessions are held psychomotor activities every week and it can be observed that the results on Program participation have being contributing to children development and helping to overcoming the elements psychomotor and social relations.